Development of STEM-Based VARK Learning Application to Improve Problem-Solving Skills in Calculus Courses - Nurmawati Nurmawati; Sri Kadarwati; Eko Andy Purnomo; Venissa Dian Mawarsari; Martyana Prihaswati; Mazlini Binti Adnan (Jurnal Pendidikan MIPA, 2026)
This research and development aims to develop a STEM-based VARK Learning Application to improve problem-solving skills in Calculus courses. Although the STEM approach has been widely applied in mathematics learning, and learning preferences such as VARK have been explored in various studies, both are generally studied separately and have not been integrated into structured adaptive mechanisms in digital learning products. Furthermore, the effectiveness of the learning styles approach remains debated when not implemented in a systematic instructional design. This research fills this gap by positioning VARK as a basis for differentiating the presentation of multimodal content within a STEM learning framework, explicitly integrated into features, activity flows, and problem-solving exercises within a single digital ecosystem. The development followed a 4-D model (define, design, develop, disseminate) through the stages of needs analysis, prototype design, expert validation, and limited implementation. The participants in the implementation were 50 students in the Mathematics Education program at a university in Semarang City, selected through purposive sampling. The research instruments included expert validation sheets (materials, media, evaluation) and problem-solving ability tests administered at three measurement times. Validation data were analyzed descriptively using mean scores, while changes in ability were analyzed using repeated-measures ANOVA. The results showed a validity score of 4.22 in the Highly Valid category (4 ≤ x ≤ 5) with minor revisions. The mean problem-solving ability increased from 74.5 to 81.4 and 84.9, with significant differences across groups. These findings indicate that integrating multimodal differentiation into digital STEM design has the potential to support improvements in problem-solving abilities in a limited research context. Further studies with experimental designs and larger samples are needed to strengthen the external validity of the findings. Keywords: calculus, learning application, problem solving, VARK.